Cole rewrote the quadratic function h(x) = x^2 - 6x

  1. Cole rewrote a quadratic function in vertex form. h(x)=x^2 -6x+7Cole said that the vertex is (3, 2). Is Cole correct? If not,
    1. answers icon 1 answer
    2. views icon 48 views
  2. Cole rewrote a quadratic function in vertex form.h(x) = x²-6x+7 Step 1: h (x) = (x²-6x+)+7 Step 2: h (x) = (x²-6x+9)+7-9 Step
    1. answers icon 1 answer
    2. views icon 62 views
  3. Cole rewrote a quadratic function in vertex form.h(x)= x^2−6x+7 Step 1: h(x)= (x^2−6x+ )+7 Step 2: h(x)=(x^2−6x+ 9 )+7
    1. answers icon 3 answers
    2. views icon 42 views
  4. Cole rewrote a quadratic function in vertex form.h(x)= x^2−6x+7 Step 1: h(x)= (x^2−6x+ )+7 Step 2: h(x)=(x^2−6x+ 9 )+7
    1. answers icon 1 answer
    2. views icon 41 views
  5. Cole rewrote a quadratic function in vertex form.h(x)= x^2−6x+7 Step 1: h(x)= (x^2−6x+ )+7 Step 2: h(x)=(x^2−6x+ 9 )+7
    1. answers icon 5 answers
    2. views icon 38 views
  6. Cole rewrote a quadratic function in vertex form.h(x)= x2−6x+7 Step 1: h(x)= (x2−6x+_) +7 Step 2: h(x)= (x2−6x+ 9)+7 −9
    1. answers icon 3 answers
    2. views icon 51 views
  7. Cole rewrote a quadratic function in vertex form.h(x)= x2−6x+7 Step 1: h(x)= (x2−6x+ 9 )+7 Step 2: h(x)=(x2−6x+ 9 )+7 −9
    1. answers icon 1 answer
    2. views icon 132 views
  8. Cole rewrote a quadratic function in vertex form.h(x)= x2−6x+7 Step 1: h(x)= (x2−6x+ )+7 Step 2: h(x)=(x2−6x+ 9 )+7 −9
    1. answers icon 1 answer
    2. views icon 59 views
  9. Cole rewrote the quadratic function h(x) = x^2 - 6x +7 into vertex form, Cole said the vertex is (3.2) is he correct? Show your
    1. answers icon 3 answers
    2. views icon 45 views
  10. Cole rewrote a quadratic function in vertex form. h(x)=x^2 -6 +7
    1. answers icon 1 answer
    2. views icon 25 views